Superconducting yarn and preparation method thereof

By pre-oxidizing, surface-treated and carbonizing the polyacrylonitrile filaments and metal wires of the conductive yarn, combined with 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, double-belt The grafting reaction of bond dendrimers forms a mixed yarn with high carbon fiber and metal wire, solving the problem of insufficient fracture strength of conductive yarns and achieving high-performance conductive protection effect.

CN118814330BActive Publication Date: 2025-01-07DEZHOU HUANYUAN ECOLOGICAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411296001.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The breaking strength of existing conductive yarns is low, making it difficult to meet the needs of high-performance conductive protection.

Method used

Polyacrylonitrile filaments are pre-oxidized, cut off, carded, surface-treated and stripped with metal wire, and carbonized through roving, fine yarn and winding to form a superconducting yarn with high carbon fiber and metal wire, passing through 3-tria Graft reactions of oxysilane propyl acrylate, 6-propyl-2-thiouracil, and double bond dendrimers improve binding strength and crosslinking density.

Benefits of technology

It significantly improves the fracture strength and anti-static effect of superconducting yarns, meeting the market's demand for high-performance conductive protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of conductive yarns, and specifically discloses a superconducting yarn and a preparation method thereof. The preparation method of superconducting yarn comprises the following steps: pre-oxidizing polyacrylonitrile filaments, cutting, combing cotton, and obtaining cotton strips; adding cotton strips to water for mixing, adding the first portion of 3-trimethoxysilane acrylate propyl, stirring for 1-3h, adding the second portion of 3-trimethoxysilane acrylate propyl, 6-propyl-2-thiouracil, and double-bonded dendritic amide, adding an initiator, stirring for 1-3h, taking out the cotton strips, washing, and obtaining surface-treated cotton strips; drawing the surface-treated cotton strips and metal wires to obtain mixed fibers; passing the mixed fibers through roving, spun yarn, and winding to obtain mixed yarns; carbonizing the mixed yarns to obtain superconducting yarns. The superconducting yarn obtained by the preparation method has the advantages of high breaking strength and good antistatic effect, which meets market demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conductive yarns, and more specifically, to a superconducting yarn and a preparation method thereof. Background Art

[0002] In the field of new energy and national defense security, conductive protection provides the most basic guarantee for production safety. In recent years, the country has had a great demand for conductive protective fabrics. The conductive yarn used in conductive protective fabrics must have good conductivity. The common conductive yarns on the market are mainly made of metal wire, carbon fiber or conductive polymer fiber. In order to improve the conductivity of conductive yarns, some researchers blend metal wire and carbon fiber to obtain superconducting yarn, which has good conductivity and can be used as a substitute for carbon fiber, as well as for conductive protection and conductive layer applications. However, the breaking strength of directly blending metal wire and carbon fiber is slightly poor and needs to be further improved. Summary of the invention

[0003] In order to improve the breaking strength of superconducting yarn, the present application provides a superconducting yarn and a preparation method thereof.

[0004] In a first aspect, the present application provides a method for preparing a superconducting yarn, using the following technical solution:

[0005] A method for preparing a superconducting yarn comprises the following steps:

[0006] S1, heating the polyacrylonitrile filament to 180-200°C, keeping the temperature for 20-40 minutes, heating the filament to 260-280°C, keeping the temperature for 20-40 minutes, and cooling the filament to room temperature to obtain pre-oxidized filament;

[0007] S2, cutting the pre-oxidized filaments, and then combing them to obtain cotton slivers;

[0008] S3, add cotton strips to water and mix, add the first portion of 3-trimethoxysilane propyl acrylate, stir for 1-3 hours, add the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and dendrimer with double bonds, mix, add initiator, stir for 1-3 hours, take out the cotton strips, wash, and obtain surface treated cotton strips;

[0009] S4, drawing the surface treated cotton strips and the metal wire to obtain mixed fibers;

[0010] S5, subjecting the mixed fiber to roving, spun yarn, and winding to obtain mixed yarn;

[0011] S6. Raise the temperature of the mixed yarn to 440-460° C., keep the temperature for 4-8 minutes, raise the temperature to 780-800° C., keep the temperature for 2-5 minutes, and cool down to room temperature to obtain a superconducting yarn.

[0012] By adopting the above technical scheme, the polyacrylonitrile filaments are first pre-oxidized, and then cut and combed to obtain cotton strips. Thereafter, the cotton strips are surface treated and drawn with metal wires. After roving, spun yarn, winding and carbonization, superconducting yarns with a high content of carbon fiber and metal wire are formed. The superconducting yarn contains carbon fiber and metal wire, and the mutual cooperation between the two can effectively improve the breaking strength and significantly reduce the electrostatic voltage. The breaking strength is greater than 10cN / dtex and the electrostatic voltage is less than 350V, showing the advantages of high breaking strength and good anti-static effect. It also has good conductivity and can be used as a substitute for carbon fiber, and can also be used as conductive protection and conductive layer to meet market demand and has good application prospects.

[0013] In the process of surface treatment of cotton strips, the first portion of 3-trimethoxysilane acrylate is first grafted onto the surface of the cotton strip to introduce carbon-carbon double bonds, and then the second portion of 3-trimethoxysilane acrylate, 6-propyl-2-thiouracil, and dendritic amide with double bonds are grafted by polymerization reaction, and siloxy, sulfide, oxygen, primary amine, amino, and amide groups are introduced, which can form intermolecular forces such as coordination bonds with the surface of the metal wire, greatly increase the bonding strength between the cotton strip and the metal wire, and improve the crosslinking density and integrity. In addition, 3-trimethoxysilane acrylate, 6-propyl-2-thiouracil, and dendritic amide with double bonds can also be carbonized to increase the carbon content and crosslinking density, enhance the breaking strength and antistatic effect of the superconducting yarn, and make the superconducting yarn show better comprehensive performance.

[0014] Optionally, the weight ratio of the cotton strip, the first portion of 3-trimethoxysilane propyl acrylate, the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, double-bonded dendrimer, and initiator is 100:(4-6):(2-4):(2-4):(2-4):(0.1-0.3).

[0015] By adopting the above technical scheme, the addition amounts of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, double-bonded dendrimer amide, and initiator are optimized, which facilitates grafting and surface treatment of cotton strips, ensures the surface treatment effect, and also ensures the stability and quality of superconducting yarn preparation.

[0016] Optionally, in step S3, the weight ratio of the sliver to water is 1:(7-13). In multiple embodiments, the weight ratio of the sliver to water is 1:10, and the weight ratio can also be set to 1:7, 1:8, 1:9, 1:11, 1:12, 1:13 as needed, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] Optionally, the initiator is one or more of potassium persulfate, sodium persulfate, and ammonium persulfate.

[0018] By adopting the above technical solution, the initiator is optimized, which facilitates the selection of the initiator. In addition, potassium persulfate, sodium persulfate and ammonium persulfate are abundant in sources, the raw materials are easy to obtain and the price is cheap.

[0019] Optionally, the double-bonded dendrimer amide is prepared by the following method:

[0020] T1. Add methylene succinic anhydride to toluene, add diethylenetriamine, stir for 1-3 hours, concentrate under reduced pressure, and dry to obtain an intermediate with a double bond;

[0021] T2. Add decanediamine to water at a temperature of 80-90°C, add the intermediate with double bonds, stir for 3-5 hours, concentrate under reduced pressure, and dry to obtain a dendritic amide with double bonds.

[0022] Optionally, the weight ratio of methylene succinic anhydride, diethylene triamine, and decanediamine is (6-15):(5-14):(1-3). Preferably, the weight ratio of methylene succinic anhydride, diethylene triamine, and decanediamine is (10-11):(9-10):(1-3).

[0023] By adopting the above technical scheme, methylene succinic anhydride and diethylenetriamine are mixed, and the anhydride group and the secondary amine group react to obtain an intermediate with a double bond. The intermediate with a double bond also contains carboxyl groups and amino groups. Then it is reacted with decanediamine, with decanediamine as the core, the amino groups in decanediamine react with the carboxyl groups in the intermediate with a double bond to achieve grafting, and the amino groups are reintroduced, and further amino groups react with the carboxyl groups in the intermediate with a double bond to gradually increase the branch chain to form a tree, and obtain a dendritic amide with a double bond. The dendritic amide with a double bond contains more carbon-carbon double bonds, amide groups, and amino groups. The reaction is carried out in steps, which is convenient for preparation and ensures the quality and use effect of the dendritic amide with a double bond.

[0024] In multiple embodiments, the weight ratio of methylene succinic anhydride, diethylenetriamine, and decanediamine is 10.4:9.6:2. The weight ratio can also be set to 6:5:1, 6:5:3, 6:14:1, 6:14:3, 15:5:1, 15:5:3, 15:14:1, and 15:14:3 as needed, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Optionally, the weight ratio of methylene succinic anhydride and toluene is (6-15):(70-130). Preferably, the weight ratio of methylene succinic anhydride and toluene is (10-11):(70-130). In multiple embodiments, the weight ratio of methylene succinic anhydride and toluene is 10.4:100, and the weight ratio can also be set to 6:70, 6:130, 15:70, 15:130, 10:70, 10:130, 11:70, 11:130 as needed, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Optionally, the weight ratio of the polyacrylonitrile filaments and the metal wires is (6-8):(2-4).

[0027] By adopting the above technical solution, the weight ratio of polyacrylonitrile filaments and metal wires is optimized to facilitate the preparation of superconducting yarns. In multiple embodiments, the weight ratio of polyacrylonitrile filaments and metal wires is 7:3, and the weight ratio can also be set to 6:4, 6.5:3.5, 7.5:2.5, 8:2 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Optionally, the fineness of the polyacrylonitrile filament is 0.5-1.5 dtex.

[0029] By adopting the above technical solution, the fineness of the polyacrylonitrile filament is optimized, which is convenient for the selection of the polyacrylonitrile filament, and can also stabilize the source and ensure the quality of the superconducting yarn. In multiple embodiments, the fineness of the polyacrylonitrile filament is 1 dtex, and the fineness can also be set to 0.5 dtex, 0.6 dtex, 0.7 dtex, 0.8 dtex, 0.9 dtex, 1.1 dtex, 1.2 dtex, 1.3 dtex, 1.4 dtex, 1.5 dtex as needed, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0030] Optionally, the breaking strength of the polyacrylonitrile filament is 2-4 cN / dtex. In multiple embodiments, the breaking strength of the polyacrylonitrile filament is 3 cN / dtex, and the breaking strength can also be set to 2 cN / dtex, 2.5 cN / dtex, 3.5 cN / dtex, 4 cN / dtex as needed, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Optionally, the metal wire is one or more of stainless steel wire, silver wire, copper wire, and iron wire.

[0032] By adopting the above technical solution, the metal wire is optimized, which facilitates the selection of the metal wire.

[0033] Optionally, the diameter of the metal wire is 0.013-0.09 mm.

[0034] By adopting the above technical solution, the diameter of the metal wire is optimized, which is convenient for the selection of the metal wire, and can also stabilize the source and ensure the quality of the superconducting yarn. In multiple embodiments, the diameter of the metal wire is 0.035 mm, and the diameter can also be set to 0.013 mm, 0.02 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm as needed, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0035] In step S1, in multiple embodiments, the polyacrylonitrile filaments are heated to 190°C, heat-treated for 30 minutes, heated to 270°C, heat-treated for 30 minutes, and cooled to 23°C to obtain pre-oxidized filaments. It is also possible to heat the polyacrylonitrile filaments to 180°C, heat-treated for 40 minutes, heated to 280°C, heat-treated for 20 minutes, and cooled to 23°C to obtain pre-oxidized filaments as needed. It is also possible to heat the polyacrylonitrile filaments to 200°C, heat-treated for 20 minutes, heated to 260°C, heat-treated for 40 minutes, and cooled to 23°C to obtain pre-oxidized filaments as needed. However, it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] In step S6, in multiple embodiments, the mixed yarn is heated to 450°C, kept warm for 6 minutes, heated to 790°C, kept warm for 4 minutes, and cooled to 23°C to obtain a superconducting yarn. It can also be heated to 440°C, kept warm for 8 minutes, heated to 800°C, kept warm for 2 minutes, and cooled to 23°C to obtain a superconducting yarn as needed. It can also be heated to 460°C, kept warm for 4 minutes, heated to 780°C, kept warm for 5 minutes, and cooled to 23°C to obtain a superconducting yarn as needed. However, it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] In a second aspect, the present application provides a superconducting yarn, which adopts the following technical solution:

[0038] A superconducting yarn is prepared by adopting the superconducting yarn preparation method.

[0039] In summary, this application has at least the following beneficial effects:

[0040] 1. The preparation method of the superconducting yarn of the present application comprises pre-oxidizing, cutting, combing, and surface treating the polyacrylonitrile filaments, and then drawing them with metal wires, and then forming superconducting yarns with a high content of carbon fibers and metal wires through roving, spun yarn, winding, and carbonization. The superconducting yarn contains carbon fibers and metal wires, and the mutual cooperation between the two makes the breaking strength greater than 10 cN / dtex and the electrostatic voltage less than 350V, so that the superconducting yarn exhibits the advantages of high breaking strength and good antistatic effect, meeting the market demand.

[0041] 2. During the surface treatment of the cotton strips, 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and double-bonded dendrimer amide are grafted on the surface of the cotton strips, and siloxy, sulfhydryl, oxy, primary amine, amino, and amide groups are introduced on the surface of the cotton strips. They can form intermolecular forces such as coordination bonds with the surface of the metal wire to increase the bonding strength. Moreover, after carbonization, the carbon content and cross-linking density are increased, the breaking strength and antistatic effect of the superconducting yarn are enhanced, and the superconducting yarn exhibits better comprehensive performance.

[0042] 3. The preparation method of the double-bonded dendritic amide of the present application first utilizes methylene succinic anhydride and diethylenetriamine to react to form a double-bonded intermediate, then utilizes decanediamine to react with the double-bonded intermediate, takes decanediamine as the core, gradually adds branches to form a tree, and obtains the double-bonded dendritic amide. The synthesis is carried out in steps, which is convenient for the preparation of the double-bonded dendritic amide and ensures the quality and use effect of the double-bonded dendritic amide. DETAILED DESCRIPTION

[0043] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0044] Preparation Example

[0045] Preparation Example 1

[0046] A dendritic amide with double bonds, which is prepared by the following method:

[0047] T1. Add 10.4 g of methylene succinic anhydride to 100 g of toluene at a rotation speed of 1000 r / min, and stir for 3 min. Add 9.6 g of diethylenetriamine, and stir for 2 h. Concentrate under reduced pressure to remove most of the toluene, dry and remove the residual toluene to obtain an intermediate with a double bond.

[0048] T2, at a speed of 400 r / min and a temperature of 85° C., add 2 g of decanediamine to 100 g of water and stir for 3 min. Add the double-bonded intermediate obtained in step T1, stir for 4 h, concentrate under reduced pressure to remove most of the water, dry and remove the residual water to obtain a dendritic amide with a double bond.

[0049] Example

[0050] Example 1

[0051] A superconducting yarn is prepared from polyacrylonitrile filaments and metal wires, wherein the weight ratio of the polyacrylonitrile filaments to the metal wires is 7:3.

[0052] Among them, the fineness of the polyacrylonitrile filament is 1 dtex and the breaking strength is 3 cN / dtex; the metal wire is stainless steel wire, the material of the stainless steel wire is 316L stainless steel, and the diameter of the stainless steel wire is 0.035 mm.

[0053] A method for preparing a superconducting yarn comprises the following steps:

[0054] S1. The polyacrylonitrile filaments are heated to 190°C, kept at this temperature for 30 minutes, heated to 270°C, kept at this temperature for 30 minutes, and cooled to 23°C to obtain pre-oxidized filaments.

[0055] S2. The pre-oxidized filaments are cut and then combed to obtain cotton slivers.

[0056] S3, adding the cotton strip obtained in step S2 to water at a rotation speed of 400 r / min. Then add the first portion of 3-trimethoxysilane propyl acrylate, stir for 2 hours, add the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and dendrimer with double bonds, stir for 3 minutes, add the initiator, stir for 2 hours. Then take out the cotton strip, wash it, and obtain the surface-treated cotton strip.

[0057] Among them, the weight ratio of water, cotton strips, the first part of 3-trimethoxysilane propyl acrylate, the second part of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, double-bonded dendrimer, and initiator is 1000:100:5:3:3:3:0.2, and the initiator is potassium persulfate; the double-bonded dendrimer is prepared by the method of Preparation Example 1.

[0058] S4, drawing the surface treated cotton strips and the metal wires together to obtain mixed fibers.

[0059] S5, the mixed fiber is processed through roving, spun yarn and winding to obtain mixed yarn.

[0060] S6. Raise the temperature of the mixed yarn to 450°C, keep the temperature for 6 minutes, raise the temperature to 790°C, keep the temperature for 4 minutes, and cool down to 23°C to obtain a superconducting yarn.

[0061] Example 2

[0062] A superconducting yarn, which is different from Example 1 in that step S3 in the preparation method is different.

[0063] Step S3 is specifically as follows: adding the cotton strip obtained in step S2 to water at a rotation speed of 400 r / min. Then adding the first portion of 3-trimethoxysilane propyl acrylate, stirring for 3 hours, adding the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and dendrimer with double bonds, stirring for 3 minutes, adding the initiator, stirring for 1 hour. Then taking out the cotton strip, washing, and obtaining the surface-treated cotton strip.

[0064] Among them, the weight ratio of water, cotton strips, the first part of 3-trimethoxysilane propyl acrylate, the second part of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, double-bonded dendrimer, and initiator is 1000:100:4:4:4:2:0.1, and the initiator is potassium persulfate; the double-bonded dendrimer is prepared by the method of Preparation Example 1.

[0065] Example 3

[0066] A superconducting yarn, which is different from Example 1 in that step S3 in the preparation method is different.

[0067] Step S3 is specifically as follows: adding the cotton strip obtained in step S2 to water at a rotation speed of 400 r / min. Then adding the first portion of 3-trimethoxysilane propyl acrylate, stirring for 1 hour, adding the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and dendrimer with double bonds, stirring for 3 minutes, adding the initiator, and stirring for 3 hours. Then taking out the cotton strip, washing, and obtaining the surface-treated cotton strip.

[0068] Among them, the weight ratio of water, cotton strips, the first part of 3-trimethoxysilane propyl acrylate, the second part of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, double-bonded dendrimer, and initiator is 1000:100:6:2:2:4:0.3, and the initiator is potassium persulfate; the double-bonded dendrimer is prepared by the method of Preparation Example 1.

[0069] Comparative Example

[0070] Comparative Example 1

[0071] A superconducting yarn, which is different from Example 1 in that, in the preparation method, step S5 and step S6 are different.

[0072] Step S5 and step S6 specifically include: subjecting the mixed fiber to roving, spun yarn, and winding to obtain superconducting yarn.

[0073] Comparative Example 2

[0074] A superconducting yarn, which differs from Example 1 in that, in the preparation method, in step S3, the first portion of 3-trimethoxysilane propyl acrylate, the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and the double-bonded dendrimer are replaced with an equal amount of water.

[0075] Comparative Example 3

[0076] A superconducting yarn, which differs from Example 1 in that, in the preparation method, in step S3, an equal amount of a second portion of 3-trimethoxysilane propyl acrylate is used to replace 6-propyl-2-thiouracil and a double-bonded dendrimer.

[0077] Comparative Example 4

[0078] A superconducting yarn, which differs from Example 1 in that, in the preparation method, in step S3, an equal amount of 6-propyl-2-thiouracil is used to replace the double-bonded dendrimer amide.

[0079] Comparative Example 5

[0080] A superconducting yarn, which differs from Example 1 in that, in the preparation method, in step S3, 6-propyl-2-thiouracil is replaced by an equal amount of double-bonded dendrimer amide.

[0081] Performance Testing

[0082] (1) The superconducting yarns obtained in Examples 1-3 and Comparative Examples 1-5 were respectively taken, and the breaking strength of the superconducting yarns was tested according to GB / T14344-2008 "Test method for tensile properties of chemical fiber filaments". The greater the breaking strength, the better the breaking strength of the superconducting yarn. The test results are shown in Table 1.

[0083] (2) The superconducting yarns obtained in Examples 1-3 and Comparative Examples 1-5 were respectively taken and woven into fabrics using a textile machine. The electrostatic voltage of the fabrics was tested in accordance with GB / T24249-2009 "Antistatic Clean Fabrics". The smaller the electrostatic voltage, the better the antistatic effect of the superconducting yarn. The test results are shown in Table 1.

[0084] (3) The superconducting yarns obtained in Examples 1-3 and Comparative Examples 1-5 were respectively taken and woven into fabrics using a textile machine. The elastic recovery rate of the fabrics was tested in accordance with FZ / T01034-2008 "Test Method for Tensile Elasticity of Woven Fabrics of Textiles". The larger the elastic recovery rate, the better the tensile elasticity of the superconducting yarn. The test results are shown in Table 1.

[0085] Table 1 Test results

[0086]

[0087] As can be seen from Table 1, the superconducting yarn of the present application has high breaking strength and elastic recovery rate. The breaking strength is 10.21-10.34 cN / dtex and the elastic recovery rate is 99.5-99.6%, showing the advantages of high breaking strength and good tensile elasticity. It also has a low electrostatic voltage of 324-332 V, showing the advantage of good anti-static effect, meeting market demand, and has good application prospects.

[0088] Comparing Example 1 with Comparative Example 1, in the preparation method of the superconducting yarn of Comparative Example 1, carbonization is not performed after winding; in the preparation method of the superconducting yarn of Example 1, carbonization is performed after winding. It can be seen that after the cotton sliver and the metal wire are drawn, the temperature is raised to 790°C for treatment, which can carbonize the cotton sliver to form a superconducting yarn with a high content of carbon fiber and metal wire, which can effectively improve the breaking strength and significantly reduce the static voltage.

[0089] Comparing Comparative Examples 2-3, in the method for preparing superconducting yarn in Comparative Example 2, in step S3, water is used to surface treat the cotton strips; in the method for preparing superconducting yarn in Comparative Example 3, in step S3, 3-trimethoxysilane propyl acrylate is used to surface treat the cotton strips. It can be seen from this that surface treatment of the cotton strips can also improve the breaking strength and reduce the static voltage. Combined with Comparative Examples 4-5 and Example 1, in Comparative Example 4, 3-trimethoxysilane propyl acrylate and 6-propyl-2-thiouracil are used to surface treat the cotton strips; in Comparative Example 5, 3-trimethoxysilane propyl acrylate and double-bonded dendrimer are used to surface treat the cotton strips; in Example 1, 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil and double-bonded dendrimer are used to surface treat the cotton strips. It can be seen from this that on the basis of using 3-trimethoxysilane propyl acrylate to treat the cotton sliver surface, 6-propyl-2-thiouracil and double-bonded dendrimer are further used to treat the cotton sliver surface, and active groups are introduced on the surface of the cotton sliver to increase the bonding strength between the cotton sliver and the metal wire. At the same time, 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil and double-bonded dendrimer can also be carbonized to increase the carbon content, increase the cross-linking density, improve the breaking strength and anti-static effect, so that the superconducting yarn exhibits better comprehensive performance.

[0090] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A method for preparing a superconducting yarn, characterized in that: The steps include: S1, heating the polyacrylonitrile filament to 180-200°C, keeping the temperature for 20-40 minutes, heating the filament to 260-280°C, keeping the temperature for 20-40 minutes, and cooling the filament to room temperature to obtain pre-oxidized filament; S2, cutting the pre-oxidized filaments, and then combing them to obtain cotton slivers; S3, add cotton strips to water and mix, add the first portion of 3-trimethoxysilane propyl acrylate, stir for 1-3 hours, add the second portion of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, and dendrimer with double bonds, mix, add initiator, stir for 1-3 hours, take out the cotton strips, wash, and obtain surface treated cotton strips; S4, drawing the surface treated cotton strips and the metal wire to obtain mixed fibers; S5, subjecting the mixed fiber to roving, spun yarn, and winding to obtain mixed yarn; S6, heating the mixed yarn to 440-460° C., keeping the temperature for 4-8 min, heating it to 780-800° C., keeping the temperature for 2-5 min, and cooling it to room temperature to obtain a superconducting yarn; The weight ratio of the cotton strip, the first part of 3-trimethoxysilane propyl acrylate, the second part of 3-trimethoxysilane propyl acrylate, 6-propyl-2-thiouracil, the double-bonded dendrimer, and the initiator is 100:(4-6):(2-4):(2-4):(2-4):(0.1-0.3); The double-bonded dendrimer is prepared by the following method: T1. Add methylene succinic anhydride to toluene, add diethylenetriamine, stir for 1-3 hours, concentrate under reduced pressure, and dry to obtain an intermediate with a double bond; T2. Add decanediamine to water at a temperature of 80-90°C, add the double-bonded intermediate, stir for 3-5 hours, concentrate under reduced pressure, and dry to obtain a dendrimer amide with a double bond; The weight ratio of the methylene succinic anhydride, diethylenetriamine and decanediamine is (6-15):(5-14):(1-3).

2. The method for preparing a superconducting yarn according to claim 1, characterized in that: The initiator is one or more of potassium persulfate, sodium persulfate and ammonium persulfate.

3. The method for preparing a superconducting yarn according to claim 1, characterized in that: The fineness of the polyacrylonitrile filament is 0.5-1.5 dtex.

4. The method for preparing a superconducting yarn according to claim 1, characterized in that: The metal wire is one or more of stainless steel wire, silver wire, copper wire and iron wire.

5. The method for preparing a superconducting yarn according to claim 1, characterized in that: The diameter of the metal wire is 0.013-0.09 mm.

6. A superconducting yarn, characterized in that: The superconducting yarn is prepared by the method for preparing the superconducting yarn according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-strength high-specific-surface-area activated carbon fiber cloth and preparation method and application thereof

    CN117587563A

  • Anchor block material for water conservancy pipeline and preparation method

    CN118495900A

  • Polyacrylonitrile-based oxidized fiber spun yarn

    JP2004250814A